The effects of freshwater treatment and thermal delousing against Amoebic Gill Disease (AGD) and sea lice (L. salmonis and C. elongatus) on the gills of Atlantic salmon (Salmo salar L.), and experimental testing of the virulence of Paramoeba perurans with change in microbiota - Gjerde, Oda (The University of Bergen, 2023)
Masteroppgave i fiskehelse FISK399 MAMN-FISK